2005
DOI: 10.1093/rheumatology/keh718
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and cultural adaptation of a German version of the AIMS2-SF questionnaire (German AIMS2-SF)

Abstract: The German AIMS2-SF is a reliable and valid instrument to assess the quality of life in primary care patients suffering from OA. When addressing the different impacts of OA, the physical scale should be divided into an upper body scale and a lower body scale. The floor and ceiling effects revealed are in accordance with the disease characteristics of the study sample and do not limit the significance of the questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…The test-retest reliability of the AIMS2-SF was good to excellent, with ICCs ranging from 0.72 to 0.83. The ICC for most components reported in this study for the Persian AIMS2-SF was similar to those reported in previous studies [12,13,15,16]. OA of the knee is the most prevalent disease among adults in Iran, with reported 7-days period prevalence of symptomatic OA as high as 15.3% [27].…”
Section: Internal Consistency and Test-retest Reliabilitysupporting
confidence: 88%
See 3 more Smart Citations
“…The test-retest reliability of the AIMS2-SF was good to excellent, with ICCs ranging from 0.72 to 0.83. The ICC for most components reported in this study for the Persian AIMS2-SF was similar to those reported in previous studies [12,13,15,16]. OA of the knee is the most prevalent disease among adults in Iran, with reported 7-days period prevalence of symptomatic OA as high as 15.3% [27].…”
Section: Internal Consistency and Test-retest Reliabilitysupporting
confidence: 88%
“…These values were within the range previously reported for the AIMS2-SF [12,13,15,16]. For the social interaction scale the Cronbach's alpha was 0.71, which is higher than the majority of coefficients previously reported: the range of reported values is 0.32-0.67 [12,13,15,16].…”
Section: Internal Consistency and Test-retest Reliabilitysupporting
confidence: 78%
See 2 more Smart Citations
“…The following most commonly used instruments measuring functioning in patients with hand OA were identified in a structured literature search which has been described elsewhere33 and included in this analysis: the Health Assessment Questionnaire (HAQ),1434 the AUSCAN (AUS),1135 the Cochin (COC) scale,1236 the Functional Index of Hand OA (FIHOA; FIH),1537 the Score for Assessment and Quantification of Chronic Rheumatoid Affections of the Hands (SACRAH; SAC) questionnaire1638 and the Arthritis Impact Measurement 2 Short Form (AIMS2-SF; AIM) questionnaire 1339…”
Section: Methodsmentioning
confidence: 99%